Exploring utility of genomic epidemiology to trace origins of highly pathogenic influenza A/H7N9 in Guangdong. Issue 2 (18th December 2020) - Bai, Ru; Sikkema, Reina S; Munnink, Bas B Oude; Li, Cong Rong; Wu, Jie; Zou, Lirong; Jing, Yi; Lu, Jing; Yuan, Run Yu; Liao, Ming; Koopmans, Marion; Ke, Chang-Wen
Abstract: The first highly pathogenic (HP) influenza A/H7N9 was reported in Guangdong in January 2017. To investigate the emergence and spread of HP A/H7N9 in Guangdong province, we sequenced 297 viruses (58 HP A/H7N9, 19 low pathogenic (LP) A/H7N9, and 220 A/H9N2) during 2016–2017. Our analysis showed that during the fifth wave, three A/H7N9 lineages were co-circulating in Guangdong: the local LP Pearl River Delta (PRD) lineage (13%), the newly imported LP Yangtze River Delta (YRD) lineage (23%), and the HP YRD lineage (64%). Previously circulating YRD-lineage LP during the third wave evolved to the YRD-lineage HP A/H7N9 in Guangdong. All YRD-lineage LP detected during the fifth wave most likely originated from newly imported viruses into Guangdong. Genotype comparison of HP A/H7N9 suggests limited outward spread of HP A/H7N9 to other provinces. The distribution of HP A/H7N9 cleavage site variants on live poultry markets differed from that found in humans, suggesting a V1-type cleavage site may facilitate human infections.